In Cases of Ischemic Heart Disease, Mucosal Alterations in the Upper Gastrointestinal Tract - Ortiq o’g’li, Raupov Abdurahmon (Journal of Innovation in Education and Social Research, 2025)
This article examines the intricate connection between upper gastrointestinal tract (UGIT) abnormalities and ischemic heart disease (IHD), especially in individuals undergoing antiplatelet therapy or with atrial fibrillation. In the co-development of cardiovascular and gastrointestinal disorders, it highlights the impact of lifestyle variables, psycho-emotional stress, and Helicobacter pylori infection. For individuals with IHD and concomitant UGIT disorders, the study emphasizes the value of early diagnosis, endoscopic examination, and customized preventative measures.